Supply shocks and the persistence of inflation - Martin Sommer (The Johns Hopkins University, Department of Economics, 2002)
This paper examines the long-run effects of supply shocks (such as oil shocks) on inflation in the United States. The persistence of supply shocks in U.S. inflation fell considerably during the period of Volcker's disinflation (1979-1982). My empirical results suggest that the difference between the pre-Volcker and post-Volcker periods is attributable to the change in the behavior of inflation expectations-agents expected shocks to persist in the pre-Volcker period, but not in the post-Volcker period. I construct a simple model of how different monetary policies lead to different persistence equilibria.
Keywords: E31; E52; E58; E65; 330; inflation; supply shocks; inflation expectations; persistence; Great Inflation; Gesamtwirtschaftliches Angebot; Schock; Inflation; Inflationserwartung; Schätzung; USA